PENGEMBANGAN MODUL TERINTEGRASI AUGMENTED REALITY PADA PEMBELAJARAN MATERI SISTEM RANGKA MANUSIA SMA KELAS XI - Novita, Via Anggun; Oka, Anak Agung; Agus Sujarwanta (EDUBIOLOCK, 2025)
This research aims to produce a product in the form of an integrated Augmented Reality (AR) module that is valid based on design and material validity tests and can facilitate students and educators to learn the biology learning material on the human skeletal system. The method used in this research is research and development with a 4-D (Four D) model which consists of four main stages, namely Define, Design, Develop, and Disseminate. The results of the module assessment by material experts obtained a feasibility percentage of 100% with "very good" criteria. The assessment by design expert validators obtained a percentage of 94.3% with "very good" criteria. Modules that have been developed based on assessments by experts are then tested on students. Students' responses to the module in the language aspect obtained a percentage score of 91.33% with the criteria "very good", in the material aspect they obtained a percentage score of 88% with the criteria "very good", and in the design aspect they obtained a percentage score of 85.67% with the criteria "very good". The module results show that the integrated Augmented reality module developed is suitable for use in the learning process.